Kepuasan Pelanggan, Kualitas Pelayanan, Varian Produk, dan Kualitas Produk - Indriana Maha Resti (Universitas Pendidikan Nasional, 2021)
The purpose of this research is to find out of the effect of service quality, product variants and product quality towards customer satisfaction. this research is focused on product or buyers at Batik Fajar Indah Surakarta. This research’s type quantitative descripte. this research’s population of this study were buyers for 3 months in 2020 is 1.350 and the sample of this researched is totally 100 responden. Data collection method use questionarie method with accidental sampling technique, and analysis technique used multiple linear regression analysis. The concluded of this researched is servive quality, product variants and quality product influencences significantly towards customer satisfaction.